Influenza A viruses limit NLRP3‐NEK7‐complex formation and pyroptosis in human macrophages. (12th November 2020) - Boal‐Carvalho, Inês; Mazel‐Sanchez, Béryl; Silva, Filo; Garnier, Laure; Yildiz, Soner; Bonifacio, Joao PPL; Niu, Chengyue; Williams, Nathalia; Francois, Patrice; Schwerk, Nicolaus; Schöning, Jennifer; Carlens, Julia; et al.
Abstract: Pyroptosis is a fulminant form of macrophage cell death, contributing to release of pro‐inflammatory cytokines. In humans, it depends on caspase 1/4‐activation of gasdermin D and is characterized by the release of cytoplasmic content. Pathogens apply strategies to avoid or antagonize this host response. We demonstrate here that a small accessory protein (PB1‐F2) of contemporary H5N1 and H3N2 influenza A viruses (IAV) curtails fulminant cell death of infected human macrophages. Infection of macrophages with a PB1‐F2‐deficient mutant of a contemporary IAV resulted in higher levels of caspase‐1 activation, cleavage of gasdermin D, and release of LDH and IL‐1β. Mechanistically, PB1‐F2 limits transition of NLRP3 from its auto‐repressed and closed confirmation into its active state. Consequently, interaction of a recently identified licensing kinase NEK7 with NLRP3 is diminished, which is required to initiate inflammasome assembly. Synopsis: Contemporary influenza A viruses limit pyroptosis and IL‐1β production in human macrophages by the expression of PB1‐F2. Via its C‐terminus PB1‐F2 binds to the pyrin and LRR domains of NLRP3 and locks it in its closed confirmation. PB1‐F2 deficient influenza A viruses induce more pyroptosis in human macrophages than isogenic wildtype strains. PB1‐F2 binds to the pyrin and LRR domains of NLRP3. The NLRP3‐PB1‐F2 complex does not bind to NEK7. Abstract : Contemporary influenza A viruses limit pyroptosis and IL‐1β production in human macrophages by the expression of PB1‐F2. Via its C‐terminus PB1‐F2 binds to the pyrin and LRR domains of NLRP3 and locks it in its closed confirmation.